С.НУРЫМБЕТОВТЫҢ ПОЭМАЛАРЫНЫҢ ҚОСЫҚ ҚУРЫЛЫСЫНДАҒЫ УЙҚАС ҲӘМ ОНЫҢ ТҮРЛЕРИ - Сайымбетов, Ш.О. (SCIENCE and SOCIETY, 2017)
The article is devoted to the analysis of the versification of poems by S.Nurumbetov. Revealing the peculiarities of the versification structure of the poems, the author of the article showns using various forms of rhyme in the poet’s works. There has been used scientific-theoretical literature showing the points of view of scholars.
Keywords: people's poet; lyrics; lyric-epic; poem; versification; rhyme